2012
DOI: 10.1002/masy.201100143
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Morphological Properties of Carboxymethylcellulose/Starch Blends with or without ZnO and Their Applications as Inoculant Carrier

Abstract: Using controlled shear-rate testing ramps, this study investigates the rheological properties of carboxymethycellulose (CMC)/starch blends, with and without zinc oxide (ZnO). Viscosity decreased as the amount of starch increased and after adding 1% ZnO. The creep and recovery tests indicated that, with increasing starch content, there was a decrease in elasticity and the viscosity zero shear rate. The results also showed, in the temperature range between 25 and 70 8C, an inversion occurred in the elastic and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…Phase angle is a measure of the visco-elasticity of the starch gels and transition of from 0°to 90°indicates the transition of starch gels from solid to liquid nature. [40] In the present study, the phase angle of the starch gels ranged from 44°to 62°and differences were observed among the cultivars and also with root growth stage ( Table 3). The of VH starch was lower at 6-8 months of root maturity, but significantly higher at the final stages, that is, at 10th and 12th months.…”
Section: Rheological Propertiessupporting
confidence: 49%
“…Phase angle is a measure of the visco-elasticity of the starch gels and transition of from 0°to 90°indicates the transition of starch gels from solid to liquid nature. [40] In the present study, the phase angle of the starch gels ranged from 44°to 62°and differences were observed among the cultivars and also with root growth stage ( Table 3). The of VH starch was lower at 6-8 months of root maturity, but significantly higher at the final stages, that is, at 10th and 12th months.…”
Section: Rheological Propertiessupporting
confidence: 49%
“…Carboxymethyl cellulose is a polymer obtained from cellulose (Togrul and Arslan, 2003), used as a thickener, gelling agent and stabilizer (da Silva Coutinho, 2012;Gomez-Diaz and Navaza, 2004). Typically, CMC solutions exhibit shear thinning (Togrul and Arslan, 2003); although, depending on the conditions of technological operations, as well as carboxymethyl cellulose concentration in the solution, dilatation or thixotropy may also occur (Imeson, 2010).…”
Section: Introductionmentioning
confidence: 99%